[PP.10.06] OBESITY-DEPENDENT EFFECTS ON MMP-9 LEVELS IN RESISTANT HYPERTENSION. (September 2016) - Ritter, A.; Faria, A.; Modolo, R.; Barbaro, N.; Sabbatini, A.; Corrêa, N.; Brunelli, V.; Pires, N.; Almeida, A.; Moreno, H.
Abstract : Objective: During the inflammatory process observed in hypertension and obesity, a destruction/proteolysis occurs on the extracellular matrix by an imbalance between metalloproteinases 2 and 9 (MMP-2 and MMP-9) enzymes and their natural tissue (TIMP-2 and TIMP-1), respectively. However, the levels of these enzymes in obese RH patients have not been thoroughly investigated. We aimed with this cross-section study to evaluate the plasmatic levels of MMP-2/-9, TIMP-2/-1 and their ratios in obese and non-obese resistant hypertensive - RH (n = 122) and compare clinical and biochemical parameters. Design and method: MMPs and TIMPs levels were measured by ELISA and cardiac damage was determined by echocardiography. Results: We did not find difference in BP parameters between groups but found higher HbA1c and reactive protein C in obese compared to non-obese RH. We also found lower MMP-9 levels and MMP-9/TIMP-1 ratio in non-obese compared to obese RH subjects. Obesity influenced MMP-9 levels in RH patients (β = 20.17; S.E = 7.08, p = 0.005) independently of age, gender, race and presence of diabetes. Additionally, obese RH with left ventricular hypertrophy (LVH) had greater MMP-9 levels compared to non- obese with LHV. No relationship between MMP-2, TIMP-2 and its ratio were found in this study. Conclusions: In summary, our study suggests that MMP-9 levels are influenced specially by obesity and have an important role in cardiac damage in RH.